The structure of poetry in the collection of Lawas Kusaremen Lawas Sia by Sanapiah Amin - Maghfiroh Fajrin; Maman Suryaman (Universitas Negeri Yogyakarta, 2020)
Various of lawas Sumbawa encountered a connotative meaning of speech and contains a philosophical element. Similarly, the studies that have been encountered before, more raised elements of symbols and meanings semantically and philosophically. To get the hidden side through the lawas, then the study will be used semiotics fitting to find out what kind of relationships that exist in the structural side of the old language with the meaning of culture. In this case the researcher tries to study the text from the aspect of lawas structure to know its relation with local culture. This is done to find out what kind of system relation signature exists in the old. These signs produce the meaning of denotation, connotation. Semiology in this research was used to know the structure of lawas, cultural form and cultural messages system contained in lawas. Lawas of Kusaramen Lawas Sia had the structure of poetry consisted of physical structure and inner structure. Lawas physical structures consisted of figurative languages; rethorical language, images and inner structures, among them the poet's tone, poet's attitude, and themes.